Age‐related biological features of germ cell tumors. Issue 3 (5th December 2013) - Collinson, Kate; Murray, Matthew J.; Orsi, Nicolas M.; Cummings, Michele; Shipley, Janet; Joffe, Johnathan K.; Coleman, Nicholas; Stark, Daniel
<x xml:space="preserve">Abstract</x> Germ cell tumors (GCTs) are rare but clinically and pathologically diverse tumors that occur in an extensive range of age groups, from children to older adults and which include both seminomatous and nonseminomatous tumors. Current clinical management for both male and female teenagers and young adults (TYAs) with GCTs remains inconsistent, alternating between pediatric and adult multidisciplinary oncology teams, based on locally defined age cutoffs. Therefore, we reviewed available literature to determine the biological similarities and differences between GCTs in young children (0–12 years), TYAs (13–24 years), and older adults (>24 years). GCTs arising in pediatric and adult populations in general showed marked molecular biological differences within identical histological subtypes, whereas there was a distinct paucity of available data for GCTs in the TYA population. These findings highlight that clinical management based simply on chronological age may be inappropriate for TYA and suggests that the optimal future management of GCTs should consider specific molecular biological factors in addition to clinical parameters in the context of patient‐specific age group rather than medical specialty. © 2013 Wiley Periodicals, Inc.